WHAT IS DISCOURSE ANALYSIS - Norbayeva, Maftuna; Baratova, Madina (Maktabgacha taʼlim jurnali, 2023)
This article focuses on discourse analysis. It provides background information for those who will encounter this approach in their reading, rather than instructions for conducting such research.